[18F]FDG PET-CT Imaging of the Low Back in Persistent Spinal Pain Syndrome Type 2: A Pilot Study Towards Improved Diagnosis - Lara S. Burmeister; Richard L. Witkam; Kris C. P. Vissers; Martin Gotthardt; Dylan J. H. A. Henssen (Brain Sciences, 2025)
Background/Objectives: Diagnosis of Persistent Spinal Pain Syndrome Type 2 (PSPS-T2) currently lacks objective biomarkers. Therefore, this retrospective study aimed to investigate differences in glucose metabolism in the axial musculoskeletal system in PSPS-T2 patients by means of [18F]FDG PET-CT imaging. Methods: Nine PSPS-T2 patients (five females, four males; mean age of 53 ± 4.82 years) and nine age- and gender-matched healthy controls (five females, four males; mean age of 53 ± 3.91 years) were included. For each participant, 24 regions of interest (ROIs) were manually drawn, including areas of the vertebral endplates, the intervertebral discs, and the psoas muscles. For each ROI, the mean standardized uptake values (SUVs) were assessed. Group differences were evaluated using repeated measures ANOVA with Bonferroni-adjusted post-hoc pairwise comparisons. Additionally, Pearson correlation analyses examined associations between SUVmean values and the Numerical Rating Scale (NRS) pain scores. Results: Results demonstrated significantly higher SUVmean values in healthy controls compared to PSPS-T2 patients, particularly at the superior endplates of L4 and S1, the intervertebral discs at L4-L5 and L5-S1, and the posterior endplates of L4 and L5. Although PSPS-T2 patients exhibited higher SUVmean values than controls in the psoas muscle, these differences were not statistically significant. Additionally, no significant correlations were found between SUVmean values and NRS pain scores, suggesting that metabolic activity alone does not directly reflect pain severity. Conclusions: Despite the limited sample size of this pilot study, the metabolic fingerprint of the axial musculoskeletal system was shown to be distinctly different in PSPS-T2 patients compared to healthy controls. This could lead to an improved understanding of PSPS-T2 pathophysiology and might open new doors for better diagnosis and treatment strategies.